Patient‐centered prioritization of bladder cancer research. Issue 15 (4th May 2018) - Smith, Angela B.; Chisolm, Stephanie; Deal, Allison; Spangler, Alejandra; Quale, Diane Z.; Bangs, Rick; Jones, J. Michael; Gore, John L.
Abstract : BACKGROUND: Patient‐centered research requires the meaningful involvement of patients and caregivers throughout the research process. The objective of this study was to create a process for sustainable engagement for research prioritization within oncology. METHODS: From December 2014 to 2016, a network of engaged patients for research prioritization was created in partnership with the Bladder Cancer Advocacy Network (BCAN): the BCAN Patient Survey Network (PSN). The PSN leveraged an online bladder cancer community with additional recruitment through print advertisements and social media campaigns. Prioritized research questions were developed through a modified Delphi process and were iterated through multidisciplinary working groups and a repeat survey. RESULTS: In year 1 of the PSN, 354 patients and caregivers responded to the research prioritization survey; the number of responses increased to 1034 in year 2. The majority of respondents had non–muscle‐invasive bladder cancer (NMIBC), and the mean time since diagnosis was 5 years. Stakeholder‐identified questions for noninvasive, invasive, and metastatic disease were prioritized by the PSN. Free‐text questions were sorted with thematic mapping. Several questions submitted by respondents were among the prioritized research questions. A final prioritized list of research questions was disseminated to various funding agencies, and a highly ranked NMIBC research question was included as a priority area in the 2017 Patient‐Centered Outcomes Research Institute announcement of pragmatic trial funding. CONCLUSIONS: Patient engagement is needed to identify high‐priority research questions in oncology. The BCAN PSN provides a successful example of an engagement infrastructure for annual research prioritization in bladder cancer. The creation of an engagement network sets the groundwork for additional phases of engagement, including design, conduct, and dissemination. Cancer 2018. © 2018 American Cancer Society . Abstract : The Bladder Cancer Advocacy Network Patient Survey Network provides a successful example of an engagement infrastructure for annual research prioritization in bladder cancer. The creation of an engagement network sets the groundwork for additional phases of engagement, including design, conduct, and dissemination.